The Relationship Between Diet and the Incidence of Dyspepsia in School-Age Children (6-18 years) at the Sukabumi Health Center, A Cross-Sectional Study - Anggraeni, Reni (Journal of Applied Nursing and Health, 2025)
Background: Dyspepsia, a disorder of the upper gastrointestinal tract, is a worldwide health problem. In Indonesia, it ranks among the most frequent conditions in primary healthcare. Research on the relationship between dietary habits and dyspepsia in school-aged children, particularly in primary health centers in Sukabumi, is limited. This study aims to explore the association between irregular eating patterns and dyspepsia in this age group. Methods: This study used quantitative research with a cross-sectional design, involving 51 purposively selected children aged 6–18 years visiting the Sukabumi Public Health Center between January and March 2025. Inclusion criteria were children aged 6–18 years, with a history of dyspepsia, and willingness to participate by completing questionnaires. Exclusion criteria included diagnosis of Helicobacter pylori infection, use of gastrointestinal-impacting medications, or presence of malignant or chronic upper gastrointestinal diseases. Data were collected using a validated questionnaire adapted from prior research, demonstrating good validity and reliability. Results: From the results obtained, 12 children had a good diet was 12 people (23.5%), and 39 children had poor diets (76.5%). Meanwhile, 35 children with dyspepsia (68.6%) and children who did not experience dyspepsia were 16 people (31.4%). There was a relationship between diet and the incidence of dyspepsia in school-age children (6-18 years) at the Sukabumi Health Center, with a p-value = 0.003, which could be interpreted as (p < 0.05) or (0.003 < 0.05) Conclusion: Irregular dietary habits are linked to dyspepsia in school-aged children at the Sukabumi Health Center, emphasizing the need for healthy eating promotion in local, resource-limited settings of middle- and low-income countries.